Beam-energy dependence of identified two-particle angular correlations in √sNN=7.7-200 GeV Au + Au collisions - Adam, Jaroslav; Deppner, Ingo Martin; Weidenkaff, Philipp (Physical review, 2020)
The two-particle angular correlation functions, R2, of pions, kaons, and protons in Au + Au collisions at √sNN=7.7,11.5,14.5,19.6,27,39,62.4, and 200 GeV were measured by the STAR experiment at the BNL Relativistic Heavy Ion Collider. These correlations were measured for both like-sign and unlike-sign charge combinations and versus the centrality. The correlations of pions and kaons show the expected near-side (i.e., at small relative angles) peak resulting from short-range mechanisms. The amplitudes of these short-range correlations decrease with increasing beam energy. However, the proton correlation functions exhibit strong anticorrelations in the near-side region. This behavior is observed for the first time in an A+A collision system. The observed anticorrelation is pT independent and decreases with increasing beam energy and centrality. The experimental results are also compared to the Monte Carlo models UrQMD, Hijing, and AMPT.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 26.05.2020